Empathy and its relationship to altruistic behavior among male and female teachers Preparatory stage in Dohuk Governorate (Journal of the College of Basic Education, 2022)
The study aimed to identify the level of empathy among male and female middle school teachers in Dohuk Governorate, and to find out if there were statistically significant differences in the level of empathy according to the variables (sex, specialization, marital status) and to identify the level of altruistic behavior among the members of the research sample. Statistically significant differences according to the variables (sex, specialization, marital status). The study also aimed to identify the correlation between sympathy and altruistic behavior.